FINANCIAL PERFORMANCE ANALYSIS OF CONSTRUCTION INDUSTRY: CASE STUDY OF PT. NINDYA KARYA (PERSERO) IN PERIOD OF 2011 - 2015 - Daryanto, Wiwiek Mardawiyah; Hestiwati, Popy Oktaviabri (Emerging Markets : Business and Management Studies Journal, 2020)
Financial performance plays an important role in assessing the condition of one company, whether they are healthy or not. Every State-Owned Enterprise has an obligation to report their financial condition in reference to the Decree of Indonesia?s Ministry of Stated-Owned Enterprises No. KEP-100/MBU/2002 regarding health valuation. This study aims to investigate the performance of PT. Nindya Karya (Persero) in eyes of their financial aspect from period of 2011 to 2015. Financial Ratio Analysis (FRA) technique was used as a tool to observe the condition. Company?s published annual reports data were taken into a data collection. By utilizing the eight chosen FRA ratios, the result of the study shows good trends, meaning that it classified as Healthy condition. However, in 2011 the scoring of indicated a Less Healthy condition, which is happening due to the lowest net income compared to the other years. In other words, the company suffers from losses in the high competition between the contractors. Additionally, the result showed a significantly increased in its ratio from 2011 to 2015. This indicates that the company made an effort in improving their competencies in the globalization era. This study will beneficial the company in determining their next strategies for the future references.